Microbiologically influenced corrosion of the ST-37 carbon steel tank by Bacillus licheniformis present in biodiesel blends. (January 2023) - Pusparizkita, Yustina M.; Aslan, Christian; Schmahl, Wolfgang W.; Devianto, Hary; Harimawan, Ardiyan; Setiadi, Tjandra; Ng, Yan Jer; Bayuseno, Athanasius P.; Show, Pau Loke
Abstract: Microbiologically influenced corrosion (MIC), commonly known as biocorrosion, is a destructive phenomenon that can be initiated by the bioactivities of microbes. It can occur in the diesel mixture storage tank, especially due to the presence of biodiesel, because the biodegradability characteristic of biodiesel results in the enhancement of microbial growth and also the MIC process. The Bacillus genus, such as B. licheniformis, is one of the microbes that is detected in the diesel storage tank and can contribute to MIC pitting phenomena. This study examined biocorrosion in ST-37 carbon steel by B. licheniformis, with variation of biodiesel concentrations (B0, B15, B20, B30, and B100). The results showed that the bioactivity of B. licheniformis increased in all biodiesel concentration cultures compared to the sterile medium. Then the highest corrosion rate was found for samples dipped in the B15-blend. However, the corrosion rate decreased on the specimen immersed in the equal and higher than B20-blend, due to thicker and more uniform biofilm formation. In addition, B. licheniformis can produce γ-polyglutamate, which acts as a corrosion inhibitor. This shows that B. licheniformis -mediated biocorrosion may promote the use of the B100 product as an environmentally friendly biofuel. However, it is important to consider the effects of B. licheniformis on diesel blend medium, especially biodegradation. Furthermore, the study of the production, extraction and implementation of γ-polyglutamate as a green corrosion inhibitor may be very useful in the future as a corrosion prevention solution. Graphical abstract: Image 1 Highlights: The concentration of biodiesel can influence the phenomena of biocorrosion in the storage tank. . B. licheniformis is detected in the storage tank of the diesel blend. TPC, gravimetry, SEM, digital microscope, and FTIR analysis are used. The formation of biofilm on the metal surface can influence the pitting corrosion attack. B. licheniformis can produce γ-polyglutamate, which can inhibit corrosion.